From Traditional Farming in Morocco to Early Urban Agroecology in Northern Mesopotamia: Combining Present-day Arable Weed Surveys and Crop Isotope Analysis to Reconstruct Past Agrosystems in (Semi-)arid Regions. (2nd October 2018) - Bogaard, Amy; Styring, Amy; Ater, Mohammed; Hmimsa, Younes; Green, Laura; Stroud, Elizabeth; Whitlam, Jade; Diffey, Charlotte; Nitsch, Erika; Charles, Michael; Jones, Glynis; Hodgson, John
ABSTRACT: We integrate functional weed ecology with crop stable carbon and nitrogen isotope analysis to assess their combined potential for inferring arable land management practices in (semi-)arid regions from archaeobotanical assemblages. Weed and GIS survey of 60 cereal and pulse fields in Morocco are combined with crop sampling for stable isotope analysis to frame assessment of agricultural labour intensity in terms of manuring, irrigation, tillage and hand-weeding. Under low management intensity weed variation primarily reflects geographical differences, whereas under high management intensity fields in disparate regions have similar weed flora. Manured and irrigated oasis barley fields are clearly discriminated from less intensively manured rain-fed barley terraces in southern Morocco; when fields in northern and southern Morocco are considered together, climatic differences are superimposed on the agronomic intensity gradient. Barley δ 13 C and δ 15 N values clearly distinguish among the Moroccan regimes. An integrated approach combines crop isotope values with weed ecological discrimination of low- and high-intensity regimes across multiple studies (in southern Morocco and southern Europe). Analysis of archaeobotanical samples from EBA Tell Brak, Syria suggests that this early city was sustained through extensive (low-intensity, large-scale) cereal farming.